Combined techniques of buccal fat pad and buccal advancement flap for revision of failed oroantral fistula closure treatment - Setjadiningrat, Raden Sonny Aditya Santosa; Istadi, Didit; Arindra, Pingky Krisna; Rosanto, Yosaphat Bayu (Majalah Kedokteran Gigi Indonesia, 2024)
Oroantral fistula (OAF) is a complication of dental extraction that is defined as open pathological communication between oral cavity and sinus of the maxillary with the involvement of epithelization of a canal. Oroantral fistula will cause infection, impaired healing, and chronic sinusitis. This article reports a case of OAF in tooth 16 which occurred after 11 months following unsuccessful sinus closure treatment. Many approaches are widely used for the closure of OAF, such as using a buccal fat pad (BFP), buccal advancement flap (BAF), or a combination. This study aims to describe the combined techniques of BFP and BAF in OAF closure of large defects with a history of previous closure failure. A 31-year-old male patient came to our hospital for the presence of OAF for 2-3 weeks. The patient underwent OAC closure at another hospital 11 months prior, but the complaint recurred. Diagnosis of OAF was carried out using the Valsalva test. A combination of BFP and BAF techniques was done to close the OAF after the removal of the epithelial. Evaluation of the treatment after 30 days showed adequate healing and full closure of OAF. OAF closure with the combined techniques of BFP and BAF displays promising results for the revision of failed OAF closure treatment.